Search for pair production of scalar bottom quarks in pp̄ collisions at s=1.96TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2006)
A search for direct production of scalar bottom quarks (b) is performed with 310pb-1 of data collected by the D0 experiment in pp̄ collisions at s=1.96TeV at the Fermilab Tevatron Collider. The topology analyzed consists of two b jets and an imbalance in transverse momentum due to undetected neutralinos (χ∼10), with χ∼10 assumed to be the lightest supersymmetric particle. We find the data consistent with standard model expectations, and set a 95% C.L. exclusion domain in the (mb∼, mχ∼10) mass plane, improving significantly upon the results from run I of the Tevatron. © 2006 The American Physical Society.